Case Report: Interventional therapy for coronary artery occlusion in a 6-year-old child with Kawasaki disease - Zhao, Lu; Xie, Li-ping; He, Lan; Liang, Xue-cun; Chu, Chen; Liu, Fang (Frontiers in Pediatrics, 2022)
A 6-year-old girl was diagnosed with Kawasaki disease and bilateral giant coronary artery aneurysms at four months old and was subsequently referred to our hospital due to chest pain and T wave changes on electrocardiography. After admission, stress myocardial perfusion imaging showed reversible ischemia in multiple areas of the left ventricle. Coronary angiography revealed complete proximal segment occlusion of the left circumflex artery (LCX). The occluded LCX was recanalized by a Gaia 3rd micro-wire successfully passing through the occluded section to the distal end of the LCX, followed by sequential balloon dilation and drug-coated balloon angioplasty. Coronary angiography immediately after post-dilation and one-year follow-up angiography showed that the structure and blood flow of LCX was good. Although percutaneous coronary intervention (PCI) in pediatric patients with Kawasaki disease is limited in practice, PCI remains one of the treatment options for selected patients.